The effect of company performance and executive remuneration on employee's perceptions of fairness in the South African financial services industry - Magee, Ryan (Organisational Psychology, 2015)
The main objective of the present study, which was conducted within the South African financial services industry was to establish whether executive remuneration (consisting of basic salary and short-term incentive bonuses) and company performance (in terms of return on equity) affects employees' perceptions of fairness. In the South African context there are many senior executives that in most peoples' opinion earn excessive salaries and bonuses, this while the organisations' that they lead perform poorly. As a consequence of their organisation performing badly, employees need to be retrenched, yet executives seemingly do not forego or even reduce their salaries or bonuses in order to retain employees and improve the organisation's bottom line. The widely publisicised (often extreme) examples of this, illustrate and are explained by the disconnect that is currently taking place globally, specifically in South Africa. This disconnect is that of inequality of wealth between the rich and the poor as measured by the Gini Coefficient, in which South Africa is now ranked the most inequal country in the world. The aim of the present study is to better understand some of the dynamics that influence perceptions of fairness in such scenarios. The present study has implications for organisations in terms of distributive justice outcomes, Human Resources practices and policies, as well various impacts on employee motivation and satisfaction.